O cinema é um encontro: a audiodescrição no festival urbanocine - Barreto, Mayara Bezerra Jerônimo da Silva (2022)
The concept of communicational and cultural accessibility has been gaining ground in debates with the social networks’ popularization. People with disabilities have been giving visibility to their rights, especially those related to incentive policies of fostering the inclusion of people with disabilities and their consequent access to cultural goods and products. In the case of visually impaired people, audio description, which is an intersemiotic translation that translates images into words, is one of the resources that allows the right to information, equal opportunities, and the training of more critical citizens with a keen sense of observation. In this context, “How to make the movie theater a meeting?” is the question that challenges cultural and audiovisual filmmakers in order to provide visually impaired people with participation in this meeting. In this way, thinking about new ways of seeing and making cinema, that reorganize the existing structures and that does not focus only on the parameter of clairvoyance, is the challenge that arises. We understand that audiovisual filmmakers need to be aware of accessible communication resources so that, from there, they can begin to tread a new path of consumption and production of art and culture. The study therefore proposes experimentation in an accessible cultural context, focusing on the visually impaired audience, in order to propose the construction of a film festival that contributes to the promotion of accessible practices in audiovisual, through audiodescription. We chose as a field of investigation the third edition of the Urbancine film festival, held in 2021, organized by filmmakers from the city of Natal and which, due to the pandemic, took place hybridly, with on-line and itinerant display, presenting national and local short films. The festival also had a program of livestream with themes that discussed the experiences of the visually impaired people with the movie theater and a conversation with the directors of the displays. The subjects-participants of the research will be the filmmakers of the audiovisual collective and visually impaired spectators. This research is part of the qualitative-based paradigm, and we chose to make use of intervention research with reference to Bakhtin's epistemological reflections. As instruments for the construction and analysis of data, we activated participant observation as we collaboratively built the festival's accessibility, in addition to holding collective interviews and using the field diary. At the end, we systematized a documentary, as a way of sharing the experiences of building communicational accessibility, focusing on the audio description of the festival.